2013
DOI: 10.3724/sp.j.1145.2013.01046
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Pb~(2+) by Dried Powder of Duckweed ( Lemna aequinoctialis )

Abstract: In order to develop efficient biosorbent material for Pb 2+ removal from wastewater, this study explored the biosorption of duckweed (Lemna aequinoctialis) powder. Single-factor experiments were designed to investigate the dominant effect on Pb 2+ removal. The experimental data were fitted with adsorption kinetics and isotherms to investigate the adsorption properties. The infrared spectroscopy was used to probe the surface characteristics of the sorbent. The results of single-factor experiments suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…(Wang et al, 2014a, b;Grijalbo et al, 2016;Wang et al, 2016) of duckweed depends on the concentration of pollutants and the toxicity level of the wastewater type. Furthermore, the success of heavy metal absorption by plants is associated with the ability of a specific phenotype and genotype of the plant to absorb and translocate heavy metals (Chen et al, 2013).…”
Section: The Effects Of As 3 + CD 2 + and Pb 2 + On The Growth Of L...mentioning
confidence: 99%
“…(Wang et al, 2014a, b;Grijalbo et al, 2016;Wang et al, 2016) of duckweed depends on the concentration of pollutants and the toxicity level of the wastewater type. Furthermore, the success of heavy metal absorption by plants is associated with the ability of a specific phenotype and genotype of the plant to absorb and translocate heavy metals (Chen et al, 2013).…”
Section: The Effects Of As 3 + CD 2 + and Pb 2 + On The Growth Of L...mentioning
confidence: 99%
“…Tang et al [83] indicated dried biomass of L. punctata and S. polyrhiza to be promising adsorbents that may be used as alternative approaches for Pb 2+ removal from contaminated water. Further studies have suggested that dried powder of L. aequinoctialis and L. perpusilla effectively removes lead from aqueous solution [86,87]. Untreated dry powder of L. aequinoctialis has also proved to be a convincing adsorbent for cadmium [88].…”
Section: Non-living/dried Duckweed Biomassmentioning
confidence: 99%